ANALISIS FAMA FRENCH 5 FACTORS MODEL DALAM MEMPENGARUHI EXCESS RETURN SAHAM PADA LQ45 - Farhan Nugraha, - (2021)
This study aims to test the effectiveness of the Fama French 5 Factors Model in explaining the Excess Returns on the LQ45 index during the 2018-2020 period. The population in this study amounted to 45 companies listed on the LQ45 index. This study used purposive sampling method and obtained a sample of 30 companies. The analytical technique used is Multiple Linear Regression Analysis and there are 18 regression models consisting of portfolio regression BH, BM, BL, SH, SM, SL, BR, BMop, BW, SR, SMop, SW, BC, BMinv BA, SC, SMinv and SA. The tools used in this study are the Eviews-10 program and Microsoft Excel 2016. The results show that Fama-French 5 Factors Model had a significant positive effect on stock excess return in the entire formed portofolio